Pengaruh Tingkat Pengungkapan Corporate Social Responsibility Terhadap Asimetri Informasi pada Sektor Pertambangan dan Barang Konsumsi dengan Variabel Kontrol Firm Value dan Managerial Ownership - Stephanie Loyanaputra; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
This study aims to identify and to prove the influence of CSR disclosure on information asymmetry. CSR disclosure level measured by using the criteria of the GRI 3.1 guidelines. The asymmetry of information used in this study using the bid-ask spread. This study used control variable of firm value and managerial ownership. The research was conducted on companies listed in the Stock Exchange which have complete annual report and data on bid-ask during the period of 2008-2015. The total sample was 267 observations. The results showed that the level of CSR disclosure could reduce information asymmetry. In addition the results also showed that firm value had significant negative affect or could reduce information asymmetry, while managerial ownership had no significant positive affect or could not reduce information asymmetry.